WOMEN EMPOWERMENT THROUGH SELF-HELP GROUPS (SHGS) IN MEWAT DISTRICT OF HARYANA STATE - Neelam; Awasthi, Suneet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women’s empowerment has been visible in recent years as a focal topic in determining their status. To connect SHGs with banks, NABARD started a project in 1991 under which 500 support groups were linked with banks. Empowerment is a process of creating awareness among women through knowledge, education, and skills. While the savings made by women improve their economic status, they can also enhance their decision-making process. The objective of the analysis is intended to replicate the social impact of the self-help group of women to investigate the changes in the SHGs social clause, to assess the influence of the SHGs on the social status of individuals and to differentiate the attitude of individuals from the SHGs and their social impact. Microcredit plays an important role in promoting socio-economic development. The objective of SHG is to ensure health as well as to empower women financially.